PERAN MUI DALAM SERTIFIKASI HALAL PADA MAKANAN BAGI MASYARAKAT MUSLIM - Maulana, Tubagus Farhan (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2024)
On October 17 2019, the government through the Halal Product Guarantee Agency (BPJPH) officially took over the management of halal certification. BPJPH is tasked with providing guidance, supervision and setting halal standards. However, the role of the MUI as the institution responsible for halal labeling remains important. As time goes by, many food ingredients that are haram have emerged, including Angciu, Emulsifier E471, Lecithin, Rhum, LARD, white bristle brushes, and alcohol in medicines. LPPOM MUI is responsible for supervising these products and providing halal certificates so that Muslim consumers can consume products that are safe and comply with sharia. This research aims to analyze the role of the Indonesian Ulema Council (MUI) in the halal certification process for food products for Muslim communities in Indonesia. Halal certification is very important considering that the majority of Indonesia's population is Muslim, and halal food is a primary need that must be met in accordance with Islamic law. This research uses qualitative methods with a literature study approach. Data was obtained from various literature, official documents and regulations related to halal certification, such as Law no. 33 of 2014 concerning Halal Product Guarantees, MUI fatwa, and data from LPPOM MUI. The research results show that the MUI plays a central role in the process of determining and monitoring the halalness of food products, although after 2019, part of the authority for halal certification has been transferred to the Halal Product Guarantee Organizing Agency (BPJPH). MUI remains the institution that has the authority to determine halal fatwas and collaborates with BPJPH in the certification process. In addition, this research found that the implementation of halal certification by the MUI provides halal guarantees which can increase Muslim consumers' confidence in the products they consume, as well as support producers in meeting the halal standards that apply in Indonesia.